THE OUTCASTS OF EDUCATION: THE PERVERSE INCLUSION OF ADOLESCENTS IN YOUTH AND ADULT EDUCATION EJA - Roberto de Oliveira , Carlos (Revista Gênero e Interdisciplinaridade, 2025)
This article is part of a master’s thesis (stricto sensu) from the Graduate Program in Social Work and Social Policy, defended in 2023 at the State University of Londrina. Its objective is to present institutional violence as one of the causes identified in the research that lead adolescents to enroll in Youth and Adult Education (EJA). The reflections presented here are the result of an exploratory-descriptive qualitative study, which used data collection through a semi-structured questionnaire and autobiographical narrative interview. Content analysis was used to examine the data. The results indicated that adolescent enrollment in EJA is multifactorial, with institutional violence being one of the identified causes for school abandonment, dropout, and the failure of those who should be part of the adolescents’ protection network. The EJA modality is used as a strategy to camouflage the real factors behind the age-grade mismatch of these students.